Optical Beam Steering With an All-Silicon Particle Chain - Hao Li; Aimin Wu; Lixing You (IEEE Photonics Journal)
Optical beam steering is fundamental and important in optics and photonics. In this study, we report a nearly total negative angle refraction over a wide angle range when an optical beam passes through an all-silicon particle chain. This phenomenon is concluded as the product of an interference effect of the double modes excited in the chain, which has potential applications for on-chip beam manipulation, routing, and filtering for its simplicity and low loss nature.